Analisis Sistem Pembelajaran Tematik Sekolah Dasar (Studi Kasus Pada MIN Toweren Kabupaten Aceh Tengah) - Husna Gemasih; Laili Wahyunita (Al-Aulad: Journal of Islamic Primary Education, 2021)
The learning system is the most important role in education. MIN Toweren Aceh Tengah has a problem in the thematic learning system. Students have poor learning motivation in class. Analysis of the learning system at MIN Toweren was carried out to find its weaknesses. With the PISCES analysis method, the current performance of the learning system is the main source of problems. The results of the analysis are the basis for consideration for improvements in the learning system. The results of this study provide a solution for the development of a digital-based learning system in grade 1 mathematics thematic lessons at MIN Toweren. From the evaluation carried out on the implementation of this digital learning system, students are considered to be more motivated in learning.